1999
DOI: 10.1161/01.hyp.34.3.423
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Relationships for the Renin-Angiotensin-Aldosterone System in a Normal Population

Abstract: Abstract-The renin-angiotensin-aldosterone system plays an important role in blood pressure regulation by influencing salt-water homeostasis and vascular tone. The purpose of the present study was to search for associations of single nucleotide polymorphisms on 3 major candidate genes of this system with the plasma concentrations of the corresponding renin-angiotensin-aldosterone system components considered as quantitative phenotypes. Genotyping was performed in 114 normotensive subjects for different variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
3
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(125 citation statements)
references
References 33 publications
8
112
3
2
Order By: Relevance
“…4,28 Frequencies of G-6A in white participants of this study were similar to those in reports from Paillard et al 29 and Tang et al 30 The D allele frequency of ACE in this study was similar to that in the reports from a meta-analysis of 145 studies, 31 except for no significantly racial difference in our study. In addition to the genetic variation, a significant difference in vascular health between black and white elderly people in this study was also found to be consistent with most of the previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…4,28 Frequencies of G-6A in white participants of this study were similar to those in reports from Paillard et al 29 and Tang et al 30 The D allele frequency of ACE in this study was similar to that in the reports from a meta-analysis of 145 studies, 31 except for no significantly racial difference in our study. In addition to the genetic variation, a significant difference in vascular health between black and white elderly people in this study was also found to be consistent with most of the previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…The D allele is known to correlate with increased tissue 15 and serum ACE levels in a dose-dependent manner in various ethnic groups. [16][17][18][19] The (CT) 2 polymorphism was shown to correlate with serum ACE in French and Nigerian populations. 16,19 We also examined two Atg polymorphisms, M235T (C to T transition at position 4072) and C-532T (C to T transition in 5 0 -flanking region).…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] The (CT) 2 polymorphism was shown to correlate with serum ACE in French and Nigerian populations. 16,19 We also examined two Atg polymorphisms, M235T (C to T transition at position 4072) and C-532T (C to T transition in 5 0 -flanking region). The M235T T allele is correlated in an allelic dose-dependent manner with Atg tissue levels 20 and with increased serum levels in various ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Genotyping of the study population for the two diallelic polymorphisms in the 5 0 -flanking region (CÀ532T, GÀ6A) of the AGT gene was performed by hybridization of PCR products using allele specific oligonucleotides as described by Paillard et al 15 …”
Section: Determination Of Genotypesmentioning
confidence: 99%